Tracking the rearrangement of atomic configurations during the conversion of FAU zeolite to CHA zeolite - Muraoka, Koki; Sada, Yuki; Shimojima, Atsushi; Chaikittisilp, Watcharop; Okubo, Tatsuya (Chemical science (Cambridge), 2019)
In order to realize designed synthesis, understanding the formation mechanism of zeolites at an atomic level has long been aspired, but remains challenging due to the fact that the knowledge of atomic configurations of the species formed during the process is limited. We focus on a synthesis system that crystallizes CHA zeolite from FAU zeolite as the sole source of tetrahedral atoms of Si and Al, so that end-to-end characterization can be conducted. Solid-state 29 Si MAS NMR is followed by high-throughput computational modeling to understand how atomic configurations changed during the interzeolite conversion. This reveals that the structural motif commonly found in FAU and CHA is not preserved during the conversion; rather, there is a specific rearrangement of silicates and aluminates within the motif. The atomic configuration of CHA seems to be influenced by that of the starting FAU , considering that CHA synthesized without using FAU results in a random Al distribution. A Metropolis Monte-Carlo simulation combined with a lattice minimization technique reveals that CHA derived from FAU has energetically favorable, biased atomic locations, which could be a result of the atomic configurations of the starting FAU . These results suggest that by choosing the appropriate reactant, Al placement could be designed to enhance the targeted properties of zeolites for catalysis and adsorption.